2021
DOI: 10.1007/s00410-021-01823-3
|View full text |Cite|
|
Sign up to set email alerts
|

Partitioning of Fe2O3 in peridotite partial melting experiments over a range of oxygen fugacities elucidates ferric iron systematics in mid-ocean ridge basalts and ferric iron content of the upper mantle

Abstract: Basalts and peridotites from mid-ocean ridges record fO2 near the quartz-fayalite-magnetite buffer (QFM), but peridotite partial melting experiments have mostly been performed in graphite capsules (~ QFM-3), precluding evaluation of ferric iron’s behavior during basalt generation. We performed experiments at 1.5 GPa, 1350–1400 °C, and fO2 from about QFM-3 to QFM+3 to investigate the anhydrous partitioning behavior of Fe2O3 between silicate melts and coexisting peridotite mineral phases. We find spinel/melt par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 66 publications
3
31
1
Order By: Relevance
“…Pyroxenitic garnets contain subequal Fe and Mg components and only become almandine-rich during crystallization at low temperatures. Our measurements and the literature data show that the compatibility of Fe 2+ is greater than that of Fe 3+ in garnet [and is likely greater in cpx ( 25 , 26 )], but the partition coefficients for both species in each phase are of similar magnitudes at the conditions relevant for cumulate fractionation in primitive arc magmas. Consequently, the crystallization of garnet pyroxenites, modeled using our measured partition coefficients, will only increase the Fe 3+ /∑Fe ratio of the magma by 0.04, corresponding to a 0.8 logarithmic unit increase in the f O 2 of the residual melt after 65% fractional crystallization (Fig.…”
Section: Deep Arc Magma Chamberssupporting
confidence: 53%
See 3 more Smart Citations
“…Pyroxenitic garnets contain subequal Fe and Mg components and only become almandine-rich during crystallization at low temperatures. Our measurements and the literature data show that the compatibility of Fe 2+ is greater than that of Fe 3+ in garnet [and is likely greater in cpx ( 25 , 26 )], but the partition coefficients for both species in each phase are of similar magnitudes at the conditions relevant for cumulate fractionation in primitive arc magmas. Consequently, the crystallization of garnet pyroxenites, modeled using our measured partition coefficients, will only increase the Fe 3+ /∑Fe ratio of the magma by 0.04, corresponding to a 0.8 logarithmic unit increase in the f O 2 of the residual melt after 65% fractional crystallization (Fig.…”
Section: Deep Arc Magma Chamberssupporting
confidence: 53%
“…Both ferrous and ferric iron are compatible in garnet at these conditions, but the difference between their partition coefficients is minimal (D Fe2+grt/melt=2.1; D Fe3+grt/melt=1.4; this study). We applied D Fe3+cpx/melt between 0.3 and 0.8 ( 25 , 26 ), represented by the width of the red-orange envelope around the modeled value (solid line) of D Fe3+cpx/melt=0.6 in Fig. 3.…”
Section: Deep Arc Magma Chambersmentioning
confidence: 99%
See 2 more Smart Citations
“…Gaetani (2016) showed that (Fe 3+ /ΣFe) spin decreases with increasing temperature and pressure although there is some uncertainty about the role of f O 2 (Sorbadere et al, 2018). Of significance however, is the observation by Davis and Cottrell (2021) Lenaz et al (2007Lenaz et al ( , 2014, Rollinson et al (2017) and Perinelli et al (2012Perinelli et al ( , 2014.…”
Section: The High-fe Groupmentioning
confidence: 99%